2012
DOI: 10.1103/physreve.85.041601
|View full text |Cite
|
Sign up to set email alerts
|

Disorder trapping during crystallization of theB2-ordered NiAl compound

Abstract: Using molecular dynamics simulations, disorder trapping associated with solidification is studied for the (100), (110), and (111) growth directions in the B2 NiAl ordered alloy compound. At the high interface velocities studied we observe pronounced disorder and defect trapping, i.e., the formation of antisite defects and vacancies in the crystal at higher than equilibrium concentrations upon rapid solidification. The vacancies are located primarily on the Ni sublattice and the majority of antisite defects are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 40 publications
4
18
0
Order By: Relevance
“…This potential not only accurately reproduces various properties of crystalline NiAl but also gives a realistic description of the principal properties of the liquid NiAl, even though no liquid data were included in the fitting of the potential. In particular, the results of the MD simulations [8,[17][18][19][41][42][43] with this EAM potential of a number of properties of the liquid Ni 50 Al 50 alloy, including diffusion, were found to be in accordance with experimental data [14][15][16][44][45][46], thus demonstrating a good transferability of this potential for an atomistic simulation of liquid NiAl. The melting temperature of B2-NiAl predicted by this potential is 1520 K [17].…”
Section: Simulation and Calculation Methodssupporting
confidence: 66%
See 2 more Smart Citations
“…This potential not only accurately reproduces various properties of crystalline NiAl but also gives a realistic description of the principal properties of the liquid NiAl, even though no liquid data were included in the fitting of the potential. In particular, the results of the MD simulations [8,[17][18][19][41][42][43] with this EAM potential of a number of properties of the liquid Ni 50 Al 50 alloy, including diffusion, were found to be in accordance with experimental data [14][15][16][44][45][46], thus demonstrating a good transferability of this potential for an atomistic simulation of liquid NiAl. The melting temperature of B2-NiAl predicted by this potential is 1520 K [17].…”
Section: Simulation and Calculation Methodssupporting
confidence: 66%
“…Now, let us estimate quantitatively the variation of temperature and concentration that can be expected to form near a planar solid-liquid interface in the liquid Ni 50 Al 50 alloy model during simulation of non-equilibrium solidification. Using the maximum value of 3.74 m s −1 of the interface velocity, v int observed at undercooling ΔT ≈ 230 K [19], one can estimate the variation of temperature near a planar solid-liquid interface in the liquid Ni 50 Al 50 alloy model according to Equation (4) as dT int $ 6 K. For this estimation, beside C P % 4:32Nk B and D q ≈ 2.4×10 −7 m 2 s −1 given in Table 1, we also used: W ∼ 1 nm [18,19], T LH ¼ DH m =C P %645 K (DH m %0.24 eV is computed here), and a 1 = 0.8839 and a 2 = 0.6267 [25,26]. Meanwhile, Equation (4) shows that in this case, M 0 , derived from Equation (2), underestimates the actual kinetic growth coefficient M by about 2-3%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature survey shows that Ni vacancy concentration in NiAl compound crystals is at variance due to the specimen's thermal or mechanical treatment history as well as its shape and size, i.e. whether bulk, coarse powder, or thin film [24][25][26][27][28][29]. The vacancy concentration derived in the present work is not inconsistent with that reported by Collins and Sinha [28], who observed that Nivacancy concentration in milled NiAl compounds with compositions very close to stoichiometric 50:50 composition, is of order 1-10 at.%.…”
Section: Discussionmentioning
confidence: 99%
“…The disorder trapping was investigated from theoretic perspective by sharp interface models [2,3,6], a diffuse interface model [11] and methods of atomistic simulation [1,12]. In the present work, using an existing approach for fast phase transformations [13], a diffuse interface model results in a system of hyperbolic equations to describe (i) the rapid interface motion and (ii) the transition from ordered to disordered structures formed from undercooled liquids.…”
Section: Introductionmentioning
confidence: 99%